2022
DOI: 10.3390/catal12040385
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Approaches as a Tool to Unravel Promising Biocatalysts from Natural Resources: Soil and Water

Abstract: Natural resources are considered a promising source of microorganisms responsible for producing biocatalysts with great relevance in several industrial areas. However, a significant fraction of the environmental microorganisms remains unknown or unexploited due to the limitations associated with their cultivation in the laboratory through classical techniques. Metagenomics has emerged as an innovative and strategic approach to explore these unculturable microorganisms through the analysis of DNA extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 215 publications
0
5
0
Order By: Relevance
“…The demand for efficient glycosyl hydrolases with outstanding catalytic activity, namely hemicellulases, is crucial to facilitate the bioconversion of hemicellulose into several value-added products (Periyasamy et al 2022 ; Nargotra et al 2023 ). Xylanases with interesting catalytic features have been searched from extreme environments using metagenomic approaches (Sousa et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The demand for efficient glycosyl hydrolases with outstanding catalytic activity, namely hemicellulases, is crucial to facilitate the bioconversion of hemicellulose into several value-added products (Periyasamy et al 2022 ; Nargotra et al 2023 ). Xylanases with interesting catalytic features have been searched from extreme environments using metagenomic approaches (Sousa et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental DNA from soil, water, animal gut, industrial sewages, and extreme environments, such as composting, has been shown to have a great potential to uncover promising enzymes for biotechnological applications (Datta et al 2020 ; Sousa et al 2022 ). Due to the huge variety of microorganisms able to degrade lignocellulosic biomass involved in composting, it is considered one of the most important (bio)reactors that contribute to the renewable bioenergy on the planet.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have revealed that over 99% of prokaryotic microorganisms remain elusive through existing pure culture isolation techniques ( Tiwari et al, 2021 ). Metagenomic sequencing technology has emerged as a potent avenue to directly access functional gene sequences from environmental DNA ( Kaushal et al, 2021 ; Robinson et al, 2021 ; Sousa et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%